Parents'/Patients' Perception of the Informed Consent Process and Surgeons Accountability in Corrective Surgery for Adolescent Idiopathic Scoliosis: A Prospective Study. Issue 23 (1st December 2020) - Chan, Chris Yin Wei; Chong, Jessamine Sze Lynn; Lee, Sin Ying; Ch'ng, Pei Ying; Chung, Weng Hong; Chiu, Chee Kidd; Hasan, Mohd Shahnaz; Kwan, Mun Keong
Abstract : Study Design: Prospective study. Objective: To determine the parents'/patients' perception on the informed consent process prior to posterior spinal fusion (PSF) for adolescent idiopathic scoliosis (AIS) patients. Summary of Background Data: Understanding parents/patients perspective on the process is important in order to achieve the goal of consent and prevent medico-legal implications. Methods: Fifty AIS patients operated between August 2019 and November 2019 were prospectively recruited. Parents'/patients' perceptions on three sections were evaluated: the process of the informed consent, specific operative risk which they were most concerned with and the accountability of surgeons for the surgical risks. These data were ranked and scored using a 5-point Likert Scale. Preferences were reported in mean and standard deviation. Differences in terms of preferences were studied using One-way analysis of variance (ANOVA) analysis and deemed significant when P < 0.05. Results: There were 30 females (60.0%) and 20 males (40.0%) with a mean age of 41.8 ± 10.6 years. Majority of parents/patients preferred the inform consent to be explained more than once ( P = 0.021), once during clinic consultation and once during admission (4.2 ± 1.0). Consent taking by both attending surgeons was preferred (4.5 ± 0.6) compared with other healthcare providers, P < 0.001. Death (60.0%) and neurological deficit (30.0%) were the two most concerned surgical risks. Parents/patients would still hold the surgeon accountable for any complications despite signing the informed consent and they felt that surgeons were directly responsible for screw-related injuries (3.9 ± 0.9), neurological injury (3.8 ± 0.9), and intraoperative bleeding (3.7 ± 0.9). Conclusion: Parents/patients preferred the attending surgeons to personally explain the informed consent, more than once with the use of visual aid. They would still hold the surgeons accountable when complications occur despite acceptance of the informed consent. Level of Evidence: 2. Abstract : Supplemental Digital Content is available in the textThis was a prospective study on inform consent. Parents/patients strongly preferred both the attending surgeons to personally explain the informed consent more than once with the use of visual aid. Parents/patients would still hold the surgeons accountable when complications occur despite acceptance of the informed consent.